Forensic Identification of Decomposed Human Body through Comparison between Ante-Mortem and Post-Mortem CT Images of Frontal Sinuses: Case Report - Rhonan Ferreira Silva; Fernando Fortes Picoli; Tessa de Lucena Botelho; Roberta Gomes Resende; Ademir Franco (University of Zagreb. School of Dental Medicine, 2017)
Objective: The aim of this paper is to report on a case of positive human identification of a decomposed body after the comparison of ante-mortem (AM) and port-mortem (PM) computed tomography images of frontal sinus. Case report: An unknown, highly decomposed human body, aged between 30 and 40 years, was found in a forest region in Brazil. The dental autopsy revealed several teeth missing AM and the presence of removable partial prostheses. The search for AM data resulted in a sequence of 20 axial images of the paranasal sinuses obtained by Multislice Computed Tomography (MSCT). PM reproduction of the MSCT images was performed in order to enable a comparative identification. After a direct confrontation between AM/PM MSCT, the data were collected for morphological findings, specifically for the lateral expansion of the left lobe, the anteroposterior dimension, and the position of median and accessory septa of the sinuses. Conclusion: The importance of storing and interpreting radiographic medical data properly is highlighted in this text, thus pointing out the importance of application of forensic radiology in the field of law.